A clash of symbolic universes: Judeanism vs Hellenism - Cromhout, Markus (HTS teologiese studies, 2007)
This article investigates how Judeans responded to Hellenism in order to maintain the integrity of their ethnic identity. Judeanism and Hellenism are regarded as alternative “symbolic universes”. It is shown that Judeans used various approaches to maintain their symbolic universe. This included Berger and Luckmann’s notions of theology, nihilation and therapy, but also accommodation, adapt-ation, appropriation of Hellenistic elements, collective opposition (or ethnicism) and a reinforcement of primordial sentiments.